Characterization of visual processing in temporomandibular disorders using functional magnetic resonance imaging - Daniel E. Harper; Kaundinya Gopinath; Jeremy L. Smith; Mia Gregory; Eric Ichesco; Sharon Aronovich; Richard E. Harris; Steven E. Harte; Daniel J. Clauw; Candace C. Fleischer (Brain and Behavior, 2023)
Abstract Background and Purpose Many patients with chronic pain report hypersensitivity not only to noxious stimuli, but also to other modalities including innocuous touch, sound, and light, possibly due to differences in the processing of these stimuli. The goal of this study was to characterize functional connectivity (FC) differences between subjects with temporomandibular disorders (TMD) and pain‐free controls during a visual functional magnetic resonance imaging (fMRI) task that included an unpleasant, strobing visual stimulus. We hypothesized the TMD cohort would exhibit maladaptations in brain networks consistent with multisensory hypersensitivities observed in TMD patients. Methods This pilot study included 16 subjects, 10 with TMD and 6 pain‐free controls. Clinical pain was characterized using self‐reported questionnaires. Visual task‐based fMRI data were collected on a 3T MR scanner and used to determine differences in FC via group independent component analysis. Results Compared to controls, subjects with TMD exhibited abnormally increased FC between the default mode network and lateral prefrontal areas involved in attention and executive function, and impaired FC between the frontoparietal network and higher order visual processing areas. Conclusions The results indicate maladaptation of brain functional networks, likely due to deficits in multisensory integration, default mode network function, and visual attention and engendered by chronic pain mechanisms.